5
1
(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)
To factor the expression 15a - 25b + 20, we first look for common factors among the terms. The greatest common factor among the coefficients is 5. We can then factor out 5 to get 5(3a - 5b + 4). This is the factored form of the expression 15a - 25b + 20.
a/(3a) = 1/3
5
1
1
(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)
15a
3a squared b squared
To factor the expression 15a - 25b + 20, we first look for common factors among the terms. The greatest common factor among the coefficients is 5. We can then factor out 5 to get 5(3a - 5b + 4). This is the factored form of the expression 15a - 25b + 20.
5 x 3a= 15a
It is: 5(3a+b) when factored
Oh, what a happy little question! When we see "3a squared," we simply need to multiply 3 by a and then square the result. So, 3a squared is the same as 3 times a times a, which simplifies to 3a^2. Just like painting a beautiful landscape, math can be a lovely adventure of discovery and creativity.
5(3a - 5b + 4)
48